(untitled) (Eurasian Research Bulletin, 2023)
This article covers the current topic of the need and sources of public (state) property. The author analyzes the role of public property in modern societies and identifies key points that justify the need for its existence. The article also examines the various sources of public property, including their legislative basis, formation processes and management mechanisms. The author focuses on issues of effective use of public property for the public good, as well as problems associated with its preservation and protection. This article provides readers with an in-depth understanding of the significance of public property, its role in socio-economic development and its influence on the formation of social relations